Time budgets and at-sea behaviour of lactating female Antarctic fur seals Arctocephalus gazella at Bouvetøya - Biuw, Martin; Krafft, Bjørn A.; Hofmeyr, G. J. Greg; Lydersen, Christian; Kovacs, Kit M. (Marine ecology. Progress series, 2009)
We present the first data on attendance patterns, at-sea movements and diving behaviour of Antarctic fur seals breeding at Bouvetøya (Bouvet Island), Southern Ocean. While other colonies have been extensively studied, this remote and second largest global population remains relatively unknown. Time depth recorders and satellite relay data loggers were deployed on breeding females during the 2000–2001 and 2001–2002 summers. Attendance and foraging patterns were similar to those observed at colonies in the Scotia Sea region where Antarctic krill is the predominant prey. Early to mid-lactation trips ranged within ~100 km of the island, usually towards the west. The dominant direction shifted later in the season and the range also increased markedly to a peak between early February and early March. Solar elevation influenced arrivals and departures from the island, with most departures occurring around sunset. Diurnal variations in diving behaviour were consistent with the vertical migration of krill. Diving frequency was higher at night and diving effort peaked around morning twilight. Afternoon deep diving was common, suggesting that females might target dense daytime krill aggregations between the photic zone and the thermocline. Trip durations increased throughout early to mid-lactation, peaking in late January to early March, before again decreasing towards the end of lactation. Our results illustrate the substantial variability, both between individuals and within individuals over time, that is likely to reflect variations in prey distribution and in the growth requirements of pups. Such variations need to be taken into account when estimating habitat use and resource utilisation in marine top predators.
Publisher: Inter-Research
Keywords: Bouvetøya; krill; marin biologi; pelsseler; plankton; satellittsendere; zoologi; økologi

Vill etter krill : på ekspedisjon med G.O. SARS til Sørishavet - Iversen, Svein A (Red.); Myklevoll, Sigmund (Red.); Mæstad, Kjartan (Red.); Nøttestad, Leif (Red.) (Havforskningsinstituttet, 2009)
Keywords: Sørishavet; ekspedisjoner; euphausiacea; forskning; krill; marin biologi; marine økosystemer; plankton; raudåte

Vill etter krill : på ekspedisjon med G.O. SARS til Sørishavet - Iversen, Svein A; Myklevoll, Sigmund; Mæstad, Kjartan; Nøttestad, Leif; Alvarez, Jaime (Havforskningsinstituttet, 2009)
Keywords: Sørishavet; ekspedisjoner; krill; marin biologi; raudåte; økosystemer

Variability and predictability of Antarctic krill swarm structure - Tarling, Geraint A.; Klevjer, Thor; Fielding, Sophie; Watkins, Jon; Atkinson, Angus; Murphy, Eugene; Korb, Rebecca; Whitehouse, Mick; Leaper, Russell (Deep Sea Research Part I: Oceanographic Research Papers, 2009)
Swarming is a fundamental part of the life of Euphausia superba, yet we still know very little about what drives the considerable variability in swarm shape, size and biomass. We examined swarms across the Scotia Sea in January and February 2003 using a Simrad EK60 (38 and 120kHz) echosounder, concurrent with net sampling. The acoustic data were analysed through applying a swarm-identification algorithm and then filtering out all non-krill targets. The area, length, height, depth, packing-concentration and inter-swarm distance of 4525 swarms was derived by this method. Hierarchical clustering revealed 2 principal swarm types, which differed in both their dimensions and packing-concentrations. Type 1 swarms were generally small (<50m long) and were not very tightly packed (<10ind.m−3), whereas type 2 swarms were an order of magnitude larger and had packing concentrations up to 10 times greater. Further sub-divisions of these types identified small and standard swarms within the type 1 group and large and superswarms within the type 2 group. A minor group (swarm type 3) was also found, containing swarms that were isolated (>100km away from the next swarm). The distribution of swarm types over the survey grid was examined with respect to a number of potential explanatory variables describing both the environment and the internal-state of krill (namely maturity, body length, body condition). Most variables were spatially averaged over scales of ∼100km and so mainly had a mesoscale perspective. The exception was the level of light (photosynthetically active radiation (PAR)) for which measurements were specific to each swarm. A binary logistic model was constructed from four variables found to have significant explanatory power (P<0.05): surface fluorescence, PAR, krill maturity and krill body length. Larger (type 2) swarms were more commonly found during nighttime or when it was overcast during the day, when surface fluorescence was low, and when the krill were small and immature. A strong pattern of diel vertical migration was not observed although the larger and denser swarms tended to occur more often at night than during the day. The vast majority of krill were contained within a minor fraction of the total number of swarms. These krill-rich swarms were more common in areas dominated by small and immature krill. We propose that, at the mesoscale level, the structure of swarms switches from being predominantly large and tightly packed to smaller and more diffuse as krill grow and mature. This pattern is further modulated according to feeding conditions and then level of light.
Keywords: Scotiahavet; Sørishavet; ekkolodd; krill; marin biologi; marine økosystemer; plankton

Metabolism and biomass vertical distribution of zooplankton in the Bransfield Strait during the austral summer of 2000 - Yebra, Lidia; Hernández-León, Santiago; Almeida, Carlos; Bécognée, Pierrick (Polar Research, 2009)
The vertical distribution (0–550 m) of zooplankton biomass, and indices of respiration (electron transfer system [ETS]) and structural growth (aminoacyltRNA synthetases activity [AARS]), were studied in waters off the Antarctic Peninsula during the austral summer of 2000. The dominant species were the copepod Metridia gerlachei and the euphausiid Euphausia superba. We observed a vertical krill/copepod substitution in the water column. The zooplankton biomass in the layer at a depth of 200–500 m was of the same magnitude as the biomass in the layer at a depth of 0–200 m, indicating that biomass in the mesopelagic zone is an important fraction of the total zooplankton in Antarctic waters. The metabolic rates of the zooplankton community were sustained by less than 0.5% of the primary production in the area, suggesting that microplankton or small copepods are the main food source. Neither food availability nor predation seemed to control mesozooplankton biomass. The wide time lag between the abundance peak of the dominant copepod (M. gerlachei) and the phytoplankton bloom is suggested to be the main explanation for the low summer zooplankton biomass observed in these waters.
Keywords: Sørishavet; biomasse; fytoplankton; hydrologi; krill; metabolisme; oseanografi; zooplankton

Persistent organohalogen contaminant burdens in Antarctic krill (Euphausia superba) from the eastern Antarctic sector: A baseline study - Bengtson Nash, Susan M; Poulsen, Anita H.; Kawaguchi, So; Vetter, Walter; Schlabach, Martin (Science of the Total Environment, 2008)
A baseline for persistent organohalogen compound (POC) accumulation in the Antarctic keystone species, Antarctic krill (Euphausia superba) has been established for a 50° longitudinal range of the eastern Antarctic sector. Samples of adult krill, caught from 12 sites distributed between 30° and 80°E (60–70°S), were analysed for >100 organohalogen compounds including chlorinated pesticides, polychlorinated biphenyls (PCBs), polybrominated organic compounds and polychlorinated dibenzo-p-dioxins/furans (PCDD/Fs). Organochlorine pesticides dominated measured krill contaminant burdens with hexachlorobenzene (HCB) as the single most abundant compound quantified. Krill HCB concentrations were comparable to those detected at this trophic level in both the Arctic and temperate northwest Atlantic, lending support for the hypothesis that HCB will approach global equilibrium at a faster rate than other POCs. Para, para′-dichlorodiphenylethene (p,p′-DDE) was detected at notable concentrations. Measurements of DDT and its degradation products provide an important baseline for monitoring the temporal and geographical influence of renewed, DDT usage for malaria-control in affected southern hemisphere countries. In contrast to the Arctic, PCBs did not feature prominently in contaminant burdens of Antarctic krill. The major commercial polybrominated diphenyl ether (PBDE) congeners -99 and -47 were quantified at low background levels with clear concentration spikes observed at around 70°E , in the vicinity of modern, active research stations. The likelihood that local anthropogenic activities are supplementing low PBDE levels, delivered otherwise primarily via long range environmental transport, is discussed. The suspected naturally occurring brominated organic compound, 2,4,6-tribromoanisole (TBA), was a ubiquitous contaminant in all samples whereas the only PCDD/Fs quantifiable were trace levels of octachlorodibenzo-p-dioxin (OCDD) and 1,2,3,4,7,8/1,2,3,4,7,9-hexachlorodibenzofuran (HxCDF). With the aims of; i) Generating a robust and broadly applicable POC auditing platform for the scarcely studied eastern Antarctic sector; ii) Determining the compounds accumulating in Antarctic krill for further toxicity evaluation studies and iii) Establishing a baseline for Antarctic predator exposure to POCs, this study represents one of the most comprehensive reports of POC contamination of the Antarctic food web to date.
Keywords: Sørishavet; forurensning; krill; marine økosystemer; menneskelig påvirkning; miljøgifter; plankton; toksikologi

Decline in energy storage in the Antarctic minke whale (Balaenoptera bonaerensis) in the Southern Ocean - Konishi, Kenji; Tamura, Tsutomu; Zenitani, Ryoko; Bando, Takeharu; Kato, Hidehiro; Walløe, Lars (Polar Biology, 2008)
The annual trend in energy storage in the Antarctic minke whale was examined using catch data from all 18 survey years in the Japanese Whale Research Program (JARPA). Regression analyses clearly showed that blubber thickness, girth and fat weight have been decreasing for nearly 2 decades. The decrease per year is estimated at approximately 0.02 cm for mid-lateral blubber thickness and 17 kg for fat weight, corresponding to 9% for both measurements over the 18-year period. Furthermore, "date", "extent of diatom adhesion", "sex", "body length", "fetus length", "latitude", "age" and "longitude" were all identified as partially independent predictors of blubber thickness. The direct interpretation of this substantial decline in energy storage in terms of food availability is difficult, since no long-term krill abundance series is available. However, an increase in the abundance of krill feeders other than minke whales and a resulting decrease in the krill population must be considered as a likely explanation.
Keywords: Sørishavet; hvaler; krill; marin biologi; plankton; vågehvaler

Hilsen fra Sørishavet - Pedersen, Ronald (Berlevågingen, 2008)
Keywords: Sørishavet; forskning; krill; marinbiologi; teknologi

Rødt gull i Sørishavet - Stephansen, Susanne Moen (Polaråret: et magasin om det internasjonale polaråret 2007-2008, 2008)
En rekelignende skapning i Sørishavet er Kjell Inge Røkkes nye yndling. Den kan nemlig brukes i alt fra slankemidler til fiskefôr. Men vet vi nok om krill til å slippe trålerne løs? Forskningsskipet G.O. Sars har vært på tokt for å finne u mer.
Keywords: Sørishavet; krill; marin biologi

Blocking primers to enhance PCR amplification of rare sequences in mixed samples – a case study on prey DNA in Antarctic krill stomachs - Vestheim, Hege; Jarman, Simon N. (Frontiers in Zoology, 2008)
Identification of DNA sequence diversity is a powerful means for assessing the species present in environmental samples. The most common molecular strategies for estimating taxonomic composition depend upon PCR with universal primers that amplify an orthologous DNA region from a range of species. The diversity of sequences within a sample that can be detected by universal primers is often compromised by high concentrations of some DNA templates. If the DNA within the sample contains a small number of sequences in relatively high concentrations, then less concentrated sequences are often not amplified because the PCR favours the dominant DNA types. This is a particular problem in molecular diet studies, where predator DNA is often present in great excess of food-derived DNA.
Keywords: Scotiahavet; Sørishavet; genetikk; genetisk analyse; krill; marin biologi; plankton; taksonomi

Crustacea in Arctic and Antarctic Sea Ice: Distribution, Diet and Life History Strategies - Arndt, Carolin E.; Swadling, Kerrie M. (Advances in Marine Biology, 2006)
This review concerns crustaceans that associate with sea ice. Particular emphasis is placed on comparing and contrasting the Arctic and Antarctic sea ice habitats, and the subsequent influence of these environments on the life history strategies of the crustacean fauna. Sea ice is the dominant feature of both polar marine ecosystems, playing a central role in physical processes and providing an essential habitat for organisms ranging in size from viruses to whales. Similarities between the Arctic and Antarctic marine ecosystems include variable cover of sea ice over an annual cycle, a light regimen that can extend from months of total darkness to months of continuous light and a pronounced seasonality in primary production. Although there are many similarities, there are also major differences between the two regions: The Antarctic experiences greater seasonal change in its sea ice extent, much of the ice is over very deep water and more than 80% breaks out each year. In contrast, Arctic sea ice often covers comparatively shallow water, doubles in its extent on an annual cycle and the ice may persist for several decades. Crustaceans, particularly copepods and amphipods, are abundant in the sea ice zone at both poles, either living within the brine channel system of the ice‐crystal matrix or inhabiting the ice–water interface. Many species associate with ice for only a part of their life cycle, while others appear entirely dependent upon it for reproduction and development. Although similarities exist between the two faunas, many differences are emerging. Most notable are the much higher abundance and biomass of Antarctic copepods, the dominance of the Antarctic sea ice copepod fauna by calanoids, the high euphausiid biomass in Southern Ocean waters and the lack of any species that appear fully dependent on the ice. In the Arctic, the ice‐associated fauna is dominated by amphipods. Calanoid copepods are not tightly associated with the ice, while harpacticoids and cyclopoids are abundant. Euphausiids are nearly absent from the high Arctic. Life history strategies are variable, although reproductive cycles and life spans are generally longer than those for temperate congeners. Species at both poles tend to be opportunistic feeders and periods of diapause or other reductions in metabolic expenditure are not uncommon.
Keywords: Sørishavet; copepoder; crustacea; havis; krill; marin biologi; plankton; polarområdene; sjøis

Fiskerier i Antarktis (6.4) - Dommasnes, Are; Iversen, Svein A; Løbach, Terje (Havets ressurser 2004 (Fisken og havet : Særnummer), 2004)
Keywords: Antarktis; fangst; fiskeindustri; fiskeriforskning; krill; ressurser

Low phytoplankton biomass and ice algal blooms in the Weddell Sea during the ice-filled summer of 1997 - Hegseth, Else Nøst; Quillfeldt von, Cecilie Hellum (Antarctic Science, 2002)
The summer of 1997 was characterized by unusually large amounts of pack ice in the southeastern Weddell Sea, and less than 10% of the area that is commonly ice-free in summer was open. A modest phytoplankton bloom developed in the upper mixed layer in the northernmost area (72°S). The bloom peaked in mid-February with max chlorophyll concentrations of 1.5 μg l−1, and integrated stocks of 55–60 mg m−2. Autotrophic flagellates dominated the biomass (80–90% of the chlorophyll) at first, while diatoms increased relative to flagellates during the bloom. Nutrient deficits, however, indicated that a much larger biomass was produced than was observed. Freezing starting after mid-February probably terminated the bloom, resulting in a pelagic growth season limited in time (less than two months) and space. The sea ice had a distinct brown layer of algae, usually at 1–2 m depth, with average chlorophyll biomass of 10.3 mg m−2. The ice cover exhibited a substantial amount of ridges, with ice algae growing in cavities and other structures, but with lower biomass than in the bands. Ice algae were also found growing on the lower 2 m of the ice shelf (visible at low tide). The overall growth season in the ice lasted several months, and ice algal production may have exceeded pelagic production in the Weddell Sea during the growth season of 1997. Pennate diatoms, like Fragilariopsis curta and F. cylindrus, dominated both in ice and in open water above the pycnocline, while Phaeocystis antarctica dominated in deeper layers and in crack pools. Euphausiids, particularly young stages, were frequently observed grazing on ice algae in ridges and on all sides of the floes, (confirmed by the gut content). Ice algae would thus have served as an ample food supply for the krill in the summer of 1997.
Edition: 2004/04/22 Publisher: Cambridge University Press
Keywords: Sørishavet; Weddellhavet; fytoplankton; havis alger; hydrografi; krill; oseanografi

Metal dynamics in an Antarctic food chain - Nygård, Torgeir; Lie, Elisabeth; Røv, Nils; Steinnes, Eiliv (Marine Pollution Bulletin, 2001)
The concentrations of copper, zinc, cadmium, selenium and mercury were determined in eggs, muscle, liver, kidney and stomach content of nestlings and adults of the Antarctic petrel, Thalassoica antarctica, and its predator, the south polar skua, Chataracta maccormicki, from Svarthamaren, Dronning Maud Land, Antarctica. The dominant food of the petrels is krill, Euphausia superba. The results show relatively high levels of cadmium in krill, which is assumed to be the main reason for the high levels of cadmium in petrels and skuas. Cadmium is almost absent in eggs, but accumulates very rapidly with age in nestlings. The copper concentrations in livers of nestling petrels reach very high levels during growth. This may be seen in connection with physiological development processes. Mercury seems to be accumulated with age and between trophic levels. Among the nestlings, the mercury levels decrease with increasing age, which may be accomplished by the excretion of mercury through the growth of feathers and as a dilution effect during growth. Selenium and mercury are inversely correlated in nestlings. The levels of zinc were similar for different nestling stages and between nestlings and adults in skuas and petrels.
Keywords: Dronning Maud Land; antarktispetrell; forurensning; fugler; krill; miljøgifter; næringskjede; ornitologi

Lipids, trophic relationships, and biodiversity in Arctic and Antarctic krill - Falk-Petersen, Stig; Hagen, Wilhelm; Kattner, Gerhard; Clarke, Andrew; Sargent, John (Canadian Journal of Fisheries and Aquatic Sciences, 2000)
Environmental seasonality is a critical factor in structuring polar marine ecosystems. The extensive data now available on the lipids of Arctic and Antarctic euphausiids show that all species are characterised by a seasonally high lipid content, and neutral lipids, whether wax esters or triacylglycerols, are primarily accumulated for reproduction. The Arctic Thysanoessa inermis and the Antarctic Euphausia crystallorophias contain high levels of wax esters and higher concentrations of 18:4(n-3) and 20:5(n-3) and a lower ratio of 18:1(n-9)/(n-7) fatty acids in their neutral lipids than the Arctic Thysanoessa raschii and the Antarctic Thysanoessa macrura and Euphausia superba. Large amounts of phytol in the lipids of T. raschii and E. crystallorophias during winter suggest the ingestion of decaying algae originating in sedimenting material or in sea ice. Thysanoessa raschii, T. macrura, and E. superba have a high ratio of 18:1(n-9)/ (n-7) fatty acids, indicating animal carnivory. We conclude that T. inermis and E. crystallorophias are true high polar herbivores, while T. raschii, T. macrura, and E. superba are omnivores with a more boreal distribution. The Arctic species Thysanoessa longicaudata and Meganyctiphanes norvegica are carnivores feeding on Calanus, as indicated by high amounts of 20:1(n-9) and 22:1(n-11) fatty acids.
Keywords: Antarktis; biodiversitet; copepoder; krill; marin biologi; marine økosystemer; plankton